Mapping the Human Dimensions of Tour Guide Research: A Bibliometric Analysis (1990–2025) - Jemi Cahya Adi wijaya; Masetya Mukti; Reni Nur Jannah; Uyun Erma Malika (JURNAL ECONOMINA, 2026)
This study aims to map the development of human dimensions in tour guide research from 1990 to 2025 using a bibliometric approach. Data were collected from 655 Scopus-indexed articles and analyzed using VOSviewer and the PRISMA procedure. The results indicate a significant increase in both publications and citations over time. Network, overlay, and density visualizations identified five major human dimensions: cultural-interpretive, service, destination development, sustainability, and individual-professional dimensions. The literature is predominantly shaped by tourism perspectives, while individual professional dimensions remain relatively underexplored. These findings highlight opportunities for future research integrating Human Resource Management and Organizational Behavior perspectives.